The Influence of Corporate Social Responsibility Disclosures on Firm Value: Does Firm Maturity Matters? - Lina; Kimberly Edelweiss (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2024)
This study aims to provide empirical evidence regarding the influence of corporate social responsibility on firm value. In addition, this study also wants to prove the moderating role of firm maturity on the influence of corporate social responsibility disclosure on firm value. The research sample was all companies except the financial sector which are included in the main board listed on the Indonesia Stock Exchange from 2020 to 2022. The results of the study indicate that corporate social responsibility disclosure has a positive influence on firm value. Firm maturity has not been proven to strengthen the influence of corporate social responsibility disclosure on firm value.